Упростите выражения:1)(2m+3)(4m²-6m+9):2)(m+2a)(m²-2am+4a²):3) (16 y²+yz²+z четвёртай степени)(4y-z²).
1) (2m+3)(4m²-6m+9)=8m³-12m²+18m+12m²-18m+27=8m³+27
2) (m+2a)(m²-2am+4a²)=m³-2am²+4a²m+2am²-4a²m+8a³=8a³+m³
3) (16 y²+yz²+)(4y-z²)=64y³-16y²z²+4y²z²-y+4y-=64y³-12y²z²+3yz-
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
1) (2m+3)(4m²-6m+9)=8m³-12m²+18m+12m²-18m+27=8m³+27
2) (m+2a)(m²-2am+4a²)=m³-2am²+4a²m+2am²-4a²m+8a³=8a³+m³
3) (16 y²+yz²+
)(4y-z²)=64y³-16y²z²+4y²z²-y
+4y
-
=64y³-12y²z²+3yz
-![z^{6} z^{6}](https://tex.z-dn.net/?f=z%5E%7B6%7D)